2017
DOI: 10.1002/2017gl073308
|View full text |Cite
|
Sign up to set email alerts
|

New estimate of the current rate of sea level rise from a sea level budget approach

Abstract: We revisit the global mean sea level (GMSL) budget during the whole altimetry era (January 1993 to December 2015) using a large number of data sets. The budget approach allows quantifying the TOPEX A altimeter drift (amounting 1.5 ± 0.5 mm/yr over 1993–1998). Accounting for this correction and using ensemble means for the GMSL and components lead to closure of the sea level budget (trend of the residual time series being 0.0 ± 0.22 mm/yr). The new GMSL rate over January 1993 to December 2015 is now close to 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
216
5
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(236 citation statements)
references
References 52 publications
13
216
5
2
Order By: Relevance
“…For the v2.0 GMSL, the same trend of 3.3 mm yr −1 is found for the 1993-2003 and 2005-2015 altimetry decades, indicating a steady rise of the GMSL. However, several recent studies using different approaches suggest that an instrumental drift has affected the TOPEX-A altimeter measurements during 1993(Valladeau et al, 2012Watson et al, 2015;Dieng et al, 2017;Beckley et al, 2017). The instrumental drift of the TOPEX-A altimeter has long been known (Hayne and Handcock, 1998), leading to the switch early 1999 to the redundant TOPEX-B altimeter.…”
Section: Long-term Gmsl Evolutionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the v2.0 GMSL, the same trend of 3.3 mm yr −1 is found for the 1993-2003 and 2005-2015 altimetry decades, indicating a steady rise of the GMSL. However, several recent studies using different approaches suggest that an instrumental drift has affected the TOPEX-A altimeter measurements during 1993(Valladeau et al, 2012Watson et al, 2015;Dieng et al, 2017;Beckley et al, 2017). The instrumental drift of the TOPEX-A altimeter has long been known (Hayne and Handcock, 1998), leading to the switch early 1999 to the redundant TOPEX-B altimeter.…”
Section: Long-term Gmsl Evolutionmentioning
confidence: 99%
“…Account-ing for the TOPEX-A instrumental correction for the first 6 years of the altimetry dataset, these studies provided a revised GMSL time series that slightly reduces the average GMSL rise over the altimetry era (from 3.3 to 3.0 mm yr −1 ), but shows clear acceleration over 1993-present. Using the corrected GMSL time series, Dieng et al (2017) and Chen et al (2017) found improved closure of the sea level budget compared to the uncorrected data.…”
Section: Long-term Gmsl Evolutionmentioning
confidence: 99%
See 3 more Smart Citations